Transcriptomic and Metabolomic Analysis Reveal the Effects of Light Quality on the Growth and Lipid Biosynthesis in Chlorella pyrenoidosa - Tingting Zhu; Ge Guan; Lele Huang; Lina Wen; Linxuan Li; Maozhi Ren (Biomolecules)
Light quality has significant effects on the growth and metabolite accumulation of algal cells. However, the related mechanism has not been fully elucidated. This study reveals that both red and blue light can promote the growth and biomass accumulation of Chlorella pyrenoidosa, with the enhancing effect of blue light being more pronounced. Cultivation under blue light reduced the content of total carbohydrate in Chlorella pyrenoidosa, while increasing the content of protein and lipid. Conversely, red light decreased the content of protein and increased the content of carbohydrate and lipid. Blue light induces a shift in carbon flux from carbohydrate to protein, while red light transfers carbon flux from protein to lipid. Transcriptomic and metabolomic analysis indicated that both red and blue light positively regulate lipid synthesis in Chlorella pyrenoidosa, but they exhibited distinct impacts on the fatty acid compositions. These findings suggest that manipulating light qualities can modulate carbon metabolic pathways, potentially converting protein into lipid in Chlorella pyrenoidosa.